Quality Team Management of Chalermrushwittayakom School, Mae Hong Son Province. - Deeseesai, Pongnarin; Chotigunjara, Thammaros; Wangcham, Sangwan (Journal of Humanities and Social Sciences, Rajapruk University, 2025)
This research aimed to study the management of quality teamwork and the guidelines for the development of the quality team management of Chalermratwittayakom School, Mae Hong Son Province. The target group was the administrators, teachers, educational personnel and parents, a total of 50 people by using purposive sampling. The tools used were a questionnaire and group discussion. The data were analyzed by statistical methods of arithmetic averages, standard deviations and content analysis. The result revealed that the quality team management of Chalermratwittayakom School, Mae Hong Son Province, in overall, was at the highest level (μ=4.54), consisting of planning, compliance with the plan, monitoring, evaluation, and improvement and development. The guidelines for the development of the quality team management of Chalermratwittayakom School, Mae Hong Son Province were that there should be budget allocation in line with the project by adhering to the protocol, supervising, and monitoring that everyone should participate, allowing all stakeholders to participate, express their opinions, and use the research process to develop and improve the management of the school to be effective.